HokenBot: transforming approaches with cutting-edge insurance app / Geetha Muthusamy ... [et al.] - Muthusamy, Geetha; Md Rashid, Nur Sarah; Abdul Hapidz, Abdul Hapidz; Harun, Nur Qurratu’ Aini (Universiti Teknologi MARA, Kedah, 2023)
Insurance is financial protection against unforeseen events or risks. It provides individuals and businesses with a sense of security and the ability to recover from losses and potential risks. The reason for low insurance consumers is a lack of awareness among individuals and many people are not adequately informed about the benefits and importance of insurance, which results in a lack of understanding about how insurance can safeguard their financial well-being. HokenBot is a holistic mobile application that serves as a reliable intermediary between users, AI bots (including virtual assistants and chatbots), expert insurance consultants, insurance information, and online transactions. This application aims to enhance user efficiency by providing a platform to easily search and select preferred insurance options and it boasts a novel feature in the form of AI bots, which can assist users by guiding them through a series of questions aimed at providing support, information, and personalized financial decisionmaking. Furthermore, this application also provides claim forms for users which saves much time for the user instead of meeting their agent to get the form. The application has significant potential in Malaysia, particularly in enhancing financial literacy. Despite the significance of the insurance industry in Malaysia, the insurance penetration rate in the country was only 54% in 2020, which is below the global average of 68%. Continued innovation, customer-centricity, and strategic partnerships will be key to its long-term success in the insurance industry. HokenBot contributes to SDG 9 by promoting innovation and efficiency in the insurance industry through its AI technology and streamlined platform. The commercialization prospects for this application are noteworthy, especially for individuals seeking precise insurance policies.